Acute onset of blindness secondary to a splenosystemic shunt in an adult cat. Issue 1 (26th August 2014) - Bennaim, Michael; Pivetta, Mauro; Puig, Jordi; Beltran, Elsa
Abstract : An eight‐year‐old female, spayed, domestic, shorthair cat was presented for acute onset of blindness, lethargy, dysorexia and weight loss. On the basis of clinical presentation, clinicopathological findings, liver function tests and diagnostic imaging, a diagnosis of hepatic encephalopathy secondary to the presence of a hepatic vascular anomaly was made. The patient responded successfully to medical treatment. This case raises the importance of considering a portosystemic shunt as a possible cause of acute onset of neurological signs in adult cats. Additionally, it suggests a potential good response to medical treatment for splenosystemic shunts.